2020
DOI: 10.1371/journal.pone.0227985
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal microbiome alterations during Neisseria gonorrhoeae infection

Abstract: Pharyngeal gonorrhoea is a common sexually transmitted infection among 'men having sex with other men' (MSM). Neisseria gonorrhoeae (NG) pharyngeal infections are usually characterized by the absence of symptoms, acting as an important reservoir for their further spread. To the best of our knowledge, no information about the composition of the pharyngeal microbiome during an ongoing NG infection is currently available. Therefore, in this study, we characterized the pharyngeal bacterial community profiles assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Consistent with our findings, Marangoni et al ( 42 ) reported no differences in the overall structure of the oropharyngeal microbiota in infected versus noninfected men. However, in contrast to our findings, Marangoni et al ( 42 ) found that infected men had an increased abundance of anaerobic bacteria (including Treponema , Parvimonas , and Peptococcus ) and a decreased abundance of aerobic bacteria (including Pseudomonas and Escherichia ). Although the differences between the two studies could be a result of population differences, they could also have resulted from differences in statistical method applied.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with our findings, Marangoni et al ( 42 ) reported no differences in the overall structure of the oropharyngeal microbiota in infected versus noninfected men. However, in contrast to our findings, Marangoni et al ( 42 ) found that infected men had an increased abundance of anaerobic bacteria (including Treponema , Parvimonas , and Peptococcus ) and a decreased abundance of aerobic bacteria (including Pseudomonas and Escherichia ). Although the differences between the two studies could be a result of population differences, they could also have resulted from differences in statistical method applied.…”
Section: Discussionsupporting
confidence: 93%
“…This is perhaps surprising, as N. gonorrhoeae infection has been associated with alterations in the composition of the rectal microbiome ( 41 ). Only one other study has described the oral microbiota composition in individuals with oropharyngeal gonorrhea ( 42 ). Consistent with our findings, Marangoni et al ( 42 ) reported no differences in the overall structure of the oropharyngeal microbiota in infected versus noninfected men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From what has been said so far, it is evident that both NM and GC can be found in the oro-pharynx, that represents a suitable ecological niche for Neisseria species to replicate and persist over time ( Marangoni et al., 2020a ).…”
Section: Introductionmentioning
confidence: 99%